STANDARDIZATION AND EVALUATION OF QUALITY OF THE JACKFRUIT PULP INCORPORATED ICE CREAM - C. R. RAJEESHA* (The Journal of Research ANGRAU, 2023)
Jackfruit (Artocarpus heterophyllus Lam.) is one of the most underutilised fruit containing high amounts of vitamins, minerals, phytochemicals, proteins, carbohydrates and other nutrients. During the flush season, jackfruit is inexpensive and readily available in large quantities.An infinite number of raw fruits are wasted each year, as the fruit is perishable and there are only few value added products.Ice cream is one of the most popular dairy products that is enjoyed by people of all ages. The experiment was conducted at the Department of Community Science, College of Agriculture, Kerala Agricultural University, Vellanikkara, Kerala in the year 2022.The organoleptic evaluation of the standardised ice creams was conducted in order to select the best treatment. The revealed that the selectedice cream had incorporation of 10 percent jackfruit pulp securing the highest mean score in terms of parameters like appearance (8.89), taste (8.82) and overall acceptability (8.81). These scores were significant when statistically evaluated using Kendall’s Coefficient of Concordance. The selected ice cream was subjected to physico-chemical analysisusing standard procedures along with control. The jackfruit incorporated ice cream is a nutritious delicacy with novel taste.